CARE OF NON PASSIONATE OLD PEOPLE IN KISANGANI - Antoine, MOMELA LISOMA (IJRDO - Journal of Social Science and Humanities Research, 2022)
We address this question by focusing our attention on the degree of satisfaction and appreciation of family care for elderly people. This will allow us to diagnose whether people in this non-passionate category find satisfaction or not in family care. The objective that we pursue in this work is to awaken the awareness of all family members to take care of their elderly without mistrust or social exclusion. Because the importance of life expectancy is fundamentally linked to the possibility of living a long and good life. To know that the presence of an old man in a family is a chance and a richness to which everyone aspires. And the elderly, like all other people, are also entitled to fundamental values ​​to which each person attaches great importance such as physical and moral integrity, life, equality at work, etc.